Why Does Cargo Spend Weeks in African Ports? The Case of Douala, Cameroon - Refas, Salim; Cantens, Thomas (2012)
This paper investigates the main factors explaining long container dwell times in African Ports. Using original and extensive data on container imports in the Port of Douala, it seeks to provide a basic understanding of why containers stay on average more than two weeks in gateway ports in Africa while long dwell times are widely recognized as a critical hindrance to economic development. It also demonstrates the interrelationships that exist between logistics performance of consignees, operational performance of port operators and efficiency of customs clearance operations. Shipment level analysis is used to identify the main determinants of long cargo dwell times and the impact of shipment characteristics such as fiscal regime, density of value, bulking and packaging type, last port of call, and region of origin or commodity group on cargo dwell time in ports is tested. External factors, such as performance of clearing and forwarding agents, shippers and shipping line strategies, also play an important role in the determination of long dwell times. Cargo dwell time distribution has many specificities, including broad-tail, high variance or right-censoring, which requires in-depth statistical analysis prior to any design of policy recommendations.